Development of Teaching Materials for Observation Report Texts in the Sekolahku Digital Platform Containing Local Wisdom from Surabaya - Adi Purnomo; Syamsul Sodiq; Titik Indarti (Kayon Media, 2025)
Abstract: This study addresses the limited implementation of contextual and culturally responsive learning in Indonesian language instruction, particularly in observation report texts. It aims to develop digital teaching materials integrated into the Sekolahku platform by incorporating local wisdom in line with the Merdeka Curriculum. Using the ADDIE model, data were collected through needs analysis, expert validation, and student trials. Results show high feasibility, with validation scores above 90% and student responses reaching 94.5% (very good). The findings indicate that integrating local culture and multimodal features enhances engagement, critical thinking, and contextual understanding, making the materials valid, practical, and effective for meaningful learning. Abstrak: Pembelajaran teks laporan hasil observasi masih cenderung tekstual dan kurang kontekstual sehingga belum mendukung pembelajaran bermakna sesuai Kurikulum Merdeka. Penelitian ini bertujuan mengembangkan materi ajar digital berbasis platform Sekolahku bermuatan kearifan lokal. Metode yang digunakan adalah model ADDIE melalui tahap analisis, desain, pengembangan, implementasi, dan evaluasi. Data didapatkan melalui wawancara beberapa narasumber, validasi ahli, dan uji coba kelompok kecil. Hasil menunjukkan kelayakan sangat baik dengan validasi materi 98,01%, bahasa 95,03%, media 90%, dan respons siswa 94,5%. Integrasi kearifan lokal dan fitur multimodal terbukti meningkatkan keterlibatan, pemahaman kontekstual, dan berpikir kritis siswa secara signifikan.